Penguatan Ekonomi Masyarakat Desa Melalui Pembuatan Pupuk Kompos Organik di Desa Sudipayung - Maharani Imbanagara; Dianatus Syafa'atul Maulida; Nugroho Aji Norcahyo; Aprilia Diva Fatikha Salsabila; Nurul Thoyibatul Fathonah; Mellyani Eprilia Yusuf; Putri Lestari (Lembaga Pengembangan Kinerja Dosen, 2024)
Sudipayung Village, Ngampel District, Kendal Regency, is an area with a growing agricultural sector, particularly in rice and tobacco production. The need for fertilizers that support agriculture is crucial, while household waste management has become a significant issue. This article discusses training on making organic compost as an effort to improve the community's economy through the management of organic waste. The training, which involves members of the local women's group (PKK), uses a simple decomposition method with ingredients such as shrimp paste and palm sugar as substitutes for EM-4. The resulting compost helps improve soil fertility, reduce dependency on chemical fertilizers, and create a greener and healthier environment. Additionally, this program contributes to reducing the volume of waste sent to the final disposal site (TPA), thus supporting environmental cleanliness. This training provides a double positive impact: increasing community knowledge about recycling waste and offering economic opportunities through the production of organic fertilizers.